Epidermal Growth Factor Protects Neuronal Cells In Vivo and In Vitro against Transient Forebrain Ischemia- and Free Radical-Induced Injuries - Peng, Hui; Wen, Tong-Chun; Tanaka, Junya; Maeda, Nobuji; Matsuda, Seiji; Desaki, Junzo; Sudo, Satoko; Zhang, Bo; Sakanaka, Masahiro (Journal of cerebral blood flow and metabolism, 1998)
Epidermal growth factor (EGF) has been considered to be a candidate for neurotrophic factors on the basis of the results of several in vitro studies. However, the in vivo effect of EGF on ischemic neurons as well as its mechanism of action have not been fully understood. In the present in vivo study using a gerbil ischemia model, we examined the effects of EGF on ischemia-induced learning disability and hippocampal CA1 neuron damage. Cerebroventricular infusion of EGF (24 or 120 ng/d) for 7 days to gerbils starting 2 hours before or immediately after transient forebrain ischemia caused a significant prolongation of response latency time in a passive avoidance task in comparison with the response latency of vehicle-treated ischemic animals. Subsequent histologic examinations showed that EGF effectively prevented delayed neuronal death of CA1 neurons in the stratum pyramidale and preserved synapses intact within the strata moleculare, radiatum, and oriens of the hippocampal CA1 region. In situ detection of DNA fragmentation (TUNEL staining) revealed that ischemic animals infused with EGF contained fewer TUNEL-positive neurons in the hippocampal CA1 field than those infused with vehicle alone at the seventh day after ischemia. In primary hippocampal cultures, EGF (0.048 to 6.0 ng/mL) extended the survival of cultured neurons, facilitated neurite outgrowth, and prevented neuronal damage caused by the hydroxyl radical-producing agent FeSO4 and by the peroxynitrite-producing agent 3-morpholinosydnonimine in a dose-dependent manner. Moreover, EGF significantly attenuated FeSO4-induced lipid peroxidation of cultured neurons. These findings suggest that EGF has a neuroprotective effect on ischemic hippocampal neurons in vivo possibly through inhibition of free radical neurotoxicity and lipid peroxidation.